CORRELATION BETWEEN LEADERSHIP AND COMPENSATION WITH THE SATISFATION OF THE EMPLOYEES AT PDAM TIRTA PAKUAN BOGOR - Ratno . (STIE Binaniaga, 2016)
This research is intended to evaluate and measure the relationship of leadership and ompensation with employee job satisfaction. The research object is PDAM Tirta Pakuan Bogor. The population for this study was taken PDAM Tirta Pakuan employees population 180 worker. Samples were taken as many as 100 people using stratified random sampling method in the population because there are various levels of work. Questionnaire was used as research instrument. Further, data collected was analyzed using regression equation by deployed SPSS (Statistical Package for Social Science) software.Result indicates that : First leadership with employee job satisfaction has a very significant relationship and have a contribution 21.4%. Both compensation with employee job satisfaction has significant relationships and have a contribution 26.7%. The third leadership and compensation together have a relationship and have a very significant contribution of 32.6%, the remaining 67.4% is determined by other variables not examined.Key words: Leadership, Compensation, and Job Satisfaction